Bending and tensile stressing state features of ductile iron pipe flange connections revealed from tested strain data. (October 2022) - Zhao, Jianbin; Wang, Qi; Gong, Yanfa; Zhang, Yannian; Zhou, Guangchun
Abstract: The existing theories and methods based on structural ultimate working states with empirical judgment could not estimate the load-bearing capacity of ductile iron pipe flange (DIPF) connections accurately. This paper tries to address the issue applying the novel structural stressing state theory and methods, leading to the revelation of the essential bending and tensile working features of DIPF connections. Firstly, the experimental strain data are transformed into the generalized strain energy density (GSED) values to build the stressing state modes and the characteristic parameters. Then, the Mann-Kendall criterion is adopted to detect the mutation points in the evolution curves of characteristic parameters. Correspondingly, it is verified that the evolutions of stressing state modes also present the mutation features. The mutation features are the embodiment of the natural law from quantitative change to qualitative change of a system, which defines the starting points of DIPF connections' failure processes. Furthermore, the Mann-Kendall criterion distinguishes the elastoplastic branch (EPB) points in the stressing state evolutions of DIPF connections. Both failure starting points and EPB points provide the new foundation to accurately determine the working capacities of DIPF connections and to improve their design. Highlights：: Open up the stressing state modeling and analysis of the tested strain data of DIPF connections. Find out the starting points in the bending and tensile failure processes of DIPF connections. Reveal the EPB points in the bending and tensile working processes of DIPF connections.